ANALISIS PENERAPAN AKUNTANSI BERDASARKAN SAK ETAP DAN PENILAIAN KESEHATAN KOPERASI DI KOTA LUBUKLINGGAU - Pancawat, Emmy; Aziza, Nurna; Coryanata, Isma (UNIB Press, 2017)
In this study, researchers focuced on the analysis of implementation SME’s accounting standard and healty assessment of cooperations in Lubuklinggau. Data were obtained through interviews with 14 managers of cooperatives in Lubuklinggau. The analytical method used here is a descriptive qualitative.The results showed that the application of SME’s by cooperatives in Lubuklinggau amounted to 52.21%.. This is because the educational background of the chairman and treasurer are not S1 economic accounting, the level of awareness of the cooperative members are still low on the development of cooperatives, dual position in the division of tasks, lack of training and dissemination of financial statements by the Department of Cooperatives and related agencies. The result of the calculation of the level of health cooperatives exist in healthy enough level is 65.51.